MAKNA MUTTASHIL DALAM IJAB DAN KABUL PERNIKAHAN PERSPEKTIF MAZHAB SYAFI’I - Irkham Taefuri; Misbah Khusurur (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
In marriage there are several pillars and conditions, where if one of the pillars or conditions is not fulfilled, it could make the marriage invalid according to Islamic religious law. There are four pillars of marriage, namely: bride and groom (male and female), guardian (of the bride), two witnesses, sighat (consent and acceptance). In the Ijab and Kabul contract, there are conditions that must be fulfilled in order for the marriage contract to be valid according to Sharia, namely the continuity of the Ijab and Kabul. The meaning of continuity is that there is no separation between consent and acceptance. This type of research is Library Research (Library Research). Based on the data sources that I have collected and studied, I have come up with the meaning of muttashil in the ijab and kabul perspective of the Shafi'i school which refers to the books of Al-Umm, Syarhu al-Shagir, Syarhu al-Shaghir, Buku al-Majmu' . In the book al-Majmu' by Imam Nawawi, it is explained that if the consent and acceptance are interrupted by many words and long silences, if it can indicate the groom's turning away from the consent, the marriage contract will certainly not be valid, because it is not muttashil (continued ).